2020
DOI: 10.1111/tid.13342
|View full text |Cite
|
Sign up to set email alerts
|

Trichodysplasia spinulosa: Case reports and review of literature

Abstract: Trichodysplasia spinulosa (TS) is a rare skin condition caused by trichodysplasia spinulosa-associated polyomavirus (TSPyV). It affects immunosuppressed patients, and <50 cases have been reported. The majority of these cases are seen in solid organ transplant recipients. TS often poses a diagnostic and therapeutic challenge because How to cite this article: Jose A, Dad T, Strand A, et al. Trichodysplasia spinulosa: Case reports and review of literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…5 A recent review of the literature mentioned that there are 60 reported cases. 5 Most patients are solid organ transplant recipients, 6 but TS has also been described in patients with immunosuppression due to medications, cancer, and HIV. 5 There is one reported case of TS in a patient with Gorlin's syndrome who was being treated with vismodegib for multiple basal cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent review of the literature mentioned that there are 60 reported cases. 5 Most patients are solid organ transplant recipients, 6 but TS has also been described in patients with immunosuppression due to medications, cancer, and HIV. 5 There is one reported case of TS in a patient with Gorlin's syndrome who was being treated with vismodegib for multiple basal cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…The features seen in TS relate to disruption of normal hair maturation. Trichodysplasia spinulosa characteristically presents with skin-colored or erythematous follicular papules with protruding white-yellowish keratin spines [1,5,19]. It most commonly affects the central face, but can also occur on the neck, trunk, and extremities.…”
Section: Case Discussionmentioning
confidence: 99%
“…To date, 31 cases of TS have been reported in SOT recipients [8]. TSPyV has been detected via PCR in skin specimens [9][10][11][12][13] from transplant patients, and replicative virions have been identified with electronic microscopy and immunohistochemistry [9].…”
Section: Discussionmentioning
confidence: 99%